The Effect of Blended Learning Method and Self-Efficacy on Students’ Self-Directed Learning - Hidayah, Nurul; Putri, Mauliana; Arafanianda, Sri (Yayasan Pendidikan Bima Berilmu, 2024)
This study aims to determine the effect of blended learning method and students’ self-efficacy on Self-directed Learning, as well as the combined effect of both variables on students’ self-directed learning. The research follows a quantitative approach and utilizes a survey method to collect data. The sample size consisted of 341 students which was determined using the Slovin formula with α = 5%. It comprised 219 students from MAN 1 Banda Aceh, 56 students from SMKS Pharmacy CUT Mutia, and 66 Students from Labschool (Senior high schoool). The data was obtained through the distribution of valid and reliable questionnaires and analyzed quantitatively. The questionnaire consists of 3 items: Self-Regulated Learning, adapted from Zimmerman (1989); Blended Learning, adapted from Staker & Horn (2012); and Student Self-Efficacy, adapted from Bandura (2006). A multicollinearity test was conducted to analyze the data. The results of the study showed that the blended learning method had a positive effect on students’ self-directed learning, accounting for 30.4% of the variance. The blended learning method and self-efficacy combined had a positive effect on students’ self-directed learning, accounting for 62.3% of the variance. In summary, apart from the blended learning method and self-efficacy, approximately 37.5% of other variables influenced Students’ Self-directed Learning. Self-efficacy was found to have a more dominant contribution to students’ self-directed learning compared to the blended learning method.